Implementasi Hukum Perwakafan dalam Rangka Membangun Kesadaran Hukum dan Kepastian Hukum: Studi Pelaksanaan Akta Ikrar Wakaf dan Pendaftaran Tanah Wakaf di Wilayah Kantor Urusan Agama Gunung Sugih Kabupaten Lampung Tengah - Suhairi, Suhairi (Tapis: Jurnal Penelitian Ilmiah, 2017)
This research aimed to answer the research question about how the affectivity of implementation of benefaction oath and registration of benefaction land in the area of religious affairs office of Gunung Sugih Central Lampung. The advantage of this research is that in realizing the awareness and certainty of benefaction law the conflicts of benefaction land can be avoided. This research is qualitative research which tried to reveal the benefaction management. The primary data were obtained from the research informant. The informant in this research was the chief of religious affairs office (KUA) and head of alms division and KUA of Gunung Sugih. While the second data were obtained from the books, document, and other references related to this research. The data collection method was done by interview and documentation. The data analysis process was done by making the formulation of research result implication in the ways of interpretation.The implementation of benefaction oath certificate and registration of benefaction land in the area of religious affairs office (KUA) of GunungSugih were not realized effectively. This case was based on the data of the amount of benefaction land that did not have AIW/APIW, it was about 41,9% benefaction and 43% of it did not have land certificate. This condition showed that the awareness of benefaction law in GunungSugih was not actualized. This problems caused the law certainty of land benefaction was not realized too. So that it could cause the conflict and returning the benefaction lands.